Higgidy : the cookbook : 100 recipes for pies and more - Stephens, Camilla (London : Mitchell Beazley, 2018)
Higgidy Pies are a firm British favourite. Now, founder Camilla Stephens brings you 100 easy recipes for pies, quiches, tarts, puds and more, so that you can cook your own Higgidy food at home. From simple suppers and quirky quiches to party pies and delectable desserts, this is heartwarming food for family and friends.
Easy extras and perfect pastry.
Includes index.
Keywords: Cooking; Pastry